(untitled) (Fiep Bulletin - online, 2013)
This experience report aims at presenting a methodological approach for the development of the Physical Education classes taught by teachers from five divisions of the 1st and 2nd years of high school Integrated Federal Institute of Alagoas - Maceió Campus. The study sample consisted of 200 students aged between 15 and 18 years (120 students being male and 80 female) in 2012. This practice took place in two stages, at first, the students researched and brought written rules of Popular Games to be applied to its traditional formatting, and subsequently, these activities were modified and adapted, transformed into other forms of executions. The central idea of ??this proposal is to develop methodological experience of the individual, allowing a recovery of body culture of the region where the student is inserted, and taking into account the teaching cultural diversity. The evaluation was made by surveying observation and frequency of student participation during class. It was observed an increase in direct participation of students in practical activities during physical education classes in the application of methodological strategy proposed in the study. Through this strategy of teaching Physical Education novelty recreational perspective, we reached the conclusion that games and play popular contribute in the formation of the individual, they offer different ways in solving problems, making decisions and developing new ways to practice based on the original form. Based on these results, further studies may contribute to the topic Games and Play Popular bringing a new perspective on both aspects of the game, as the social aspect.